Hubungan Efikasi Diri dengan Kematangan Karier pada Siswa Kelas XI SMA Mekar Arum Kabupaten Bandung - Aprilia, Jeni; Alfaiz, Alfaiz; Julius, Andre; Rafiola, Ryan Hidayat (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This research aims to look at the relationship between self efficacy and career maturity in students at Mekar Arum Hight School. This research uses a quantitative approach using the correlational method, and sampling using the Proportionate Statified technique. The subjects in this research were Mekar Arum Hight School students in class XI with a total of 97 students as respondents. In this study, the research instrument used a self efficacy scale, with a reliability result of 0.874 and a Career Maturity Scale with a reliability result of 0.713. These results show that there is a positive and very significant relationship between self efficacy, and career maturity in students at Mekar Arum Hight School with a Pearshon correlation coefficient = 0.507, p = 0.000. It can be concluded that there is a significant relationship between self efficacy and maturity in class XI students at Mekar Arum High School. This means that the higher the self-efficacy, the better the student’s career maturity, and cvice versa. The lower the self efficacy, the lower the student’s career maturity. According to the result self-efficacy has a significance correlation, and this is explain that self-efficacy can make great result of career maturity.